The Quality of Life of Elderly with Non-Communicable Diseases in Sinsamut Community, Pathumthani Province - Sukarnjanaset, Pattarin; Sadabpod, Kamala (Vajira Medical Journal : Journal of Urban Medicine, 2018)
Objective: To assess the Quality of Life (QoL) and the factors affecting QoL in elderly people with non-communicable diseases (NCDs) in Sinsamut community, Pathumthani province. Methods: This study surveyed elderly people with NCDs living in Sinsamut Community between August 2017 to December 2017 by using a questionnaire for the general data and the World Health Organization Quality of Life Brief – Thai (WHOQOL-BREF-THAI). The independent t-test was used to compare QoL score between the two groups studied. Results: Thirty-three elderly with NCDs participated and completed the study questionnaire. The median age was 69 years [Interquartile range (IQR) 11 years]. Most participants were female (66.7%) and entitled to universal health insurance (78.8%). The most common NCDs found in participants were hypertension (81.8%), followed by hyperlipidemia, diabetes and cardiovascular disease, respectively. The average number of medications used in participants was 4.8± Standard deviation (SD) 2.8 items. The score for overall QoL was 82.2±SD 13.1, mostly in the moderate level (78.8%). The quality of life levels for physical health, psychological, social relationships, including environmental domains, were in the moderate level. Age, sex, marital status, average monthly income, types of NCDs and numbers of diseases were not the factors that significantly affected QoL. Nevertheless, the number of medications used by participants statistically affected QoL (p<0.05). The participants who received less than 5 drugs had better overall physical health domain of QoL than those who took 5 drugs or more. Conclusion: Therefore, the emphasis on reducing unnecessary or overlapping drug orders to reduce the number of medications in the elderly with NCDs might improve patients’ QoL.